The physical and physiological demands of basketball training and competition - Montgomery, P. G.; Pyne, D. B.; Minahan, C. (International Journal of Sports Physiology and Performance, 2010)
Purpose: To characterize the physical and physiological responses during different basketball practice drills and games. Methods: Male basketball players (n = 11; 19.1 ± 2.1 y, 1.91 ± 0.09 m, 87.9 ± 15.1 kg; mean ± SD) completed offensive and defensive practice drills, half court 5on5 scrimmage play, and competitive games. Heart rate, VO2 and triaxial accelerometer data (physical demand) were normalized for individual participation time. Data were log-transformed and differences between drills and games standardized for interpretation of magnitudes and reported with the effect size (ES) statistic. Results: There was no substantial difference in the physical or physiological variables between offensive and defensive drills; physical load (9.5%; 90% confidence limits ±45); mean heart rate (-2.4%; ±4.2); peak heart rate (-0.9%; ±3.4); and VO2 (-5.7%; ±9.1). Physical load was moderately greater in game play compared with a 5on5 scrimmage (85.2%; ±40.5); with a higher mean heart rate (12.4%; ±5.4). The oxygen demand for live play was substantially larger than 5on5 (30.6%; ±15.6). Conclusions: Defensive and offensive drills during basketball practice have similar physiological responses and physical demand. Live play is substantially more demanding than a 5on5 scrimmage in both physical and physiological attributes. Accelerometers and predicted oxygen cost from heart rate monitoring systems are useful for differentiating the practice and competition demands of basketball.